THEORETICAL APPROACHES AND INTERNATIONAL EXPERIENCE IN TEACHING SCIENCES (Multidisciplinary Journal of Science and Technology, 2025)
In this thesis discussed about several interactive methods for enhancing the lesson process. Also highlighted many theory task and ways to improve their skills for future teachers and coaches. Furthermore, we discussed some useful ways of teaching students in different subjects via white boards.